Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/neuonc/noaa248
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of low-grade glioma genetic variants predicts key target genes and transcription factors

Abstract: Background Large-scale genome-wide association studies (GWAS) have implicated thousands of germline genetic variants in modulating individuals’ risk to various diseases, including cancer. At least 25 risk loci have been identified for low-grade gliomas (LGGs), but their molecular functions remain largely unknown. Methods We hypothesized that GWAS loci contain causal single nucleotide polymorphisms (SNPs) that reside in access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Besides, polymorphisms of other important genes also contribute to glioma risk. For instance, a functional SNP rs12803321 with Solute Carrier Family 25 Member 26 as the target gene was found to be a causal locus of LGG [ 12 ]. Recently, our group investigated the impacts of SNPs in the RNA m6A modification core genes on pediatric glioma susceptibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, polymorphisms of other important genes also contribute to glioma risk. For instance, a functional SNP rs12803321 with Solute Carrier Family 25 Member 26 as the target gene was found to be a causal locus of LGG [ 12 ]. Recently, our group investigated the impacts of SNPs in the RNA m6A modification core genes on pediatric glioma susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Some well-recognized genetic syndromes confer glioma risk, including the Turcot and Li-Fraumeni syndromes, neurofibromatosis type 1, and multiple enchondromatosis [8]. Moreover, numerous candidate gene association studies provide evidence of a link between genetic variation and glioma predisposition [8][9][10][11][12]. For instance, glioma susceptibility loci have been comprehensively explored in DNA repair, cell cycle, metabolism, and inflammation (including allergies and infections) pathways [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, with the combination of ATAC-seq and whole genome sequencing (WGS) data, three TERT promoter mutations were found to generate ETF motif sites, leading to an increase in TERT gene expression ( 25 ). Furthermore, an integrative analysis of ATAC-seq and gene expression data from public repositories has identified low-grade glioma GWAS variant rs648044 as a causative SNP, which perturbed the binding affinity of the TF MAFF and thus regulated the expression of ZBTB16 ( 26 ). In the present study, by integrating the ATAC-seq and ChIP-seq data, we discovered and validated a functional polymorphism rs13064999 in TP63 , which associated with NSCLC susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Although the location of rs11706832 in intron 2 of LRIG1 could indicate a role in the regulation of LRIG1 itself, the SNP is not a documented expression quantitative trait locus (eQTL) for LRIG1 , but rs11706832 affect the expression of the adjacent solute carrier family 25 member 26 gene SLC25A26 according to the GTEx database ( https://gtexportal.org/home/snp/rs11706832 ). It has previously been suggested that the rs11706832 A-C conversion would create a possible perturbation of the binding motif for the transcriptional repressor LEF1 12 13 . Public data from DNase hypersensitivity sequencing from ENCODE reveals rs11706832 lies in an open chromatin region, indicating a regulatory mechanism of the SNP.…”
Section: Introductionmentioning
confidence: 99%